Effect of Partial Oxygen Supply on Mitochondrial Electron Transport System During Complete Cardiac Ischemia - (:unkn) unknown (My University, 1985)
Abstract During complete ischemia we assessed myocardial utilization of the small amount of oxygen available. We also determined whether blood cardioplegia has any advantage over crystalloid cardioplegia in this setting. Patients with preserved left ventricular myocardial function and without anterolateral wall infarct or aneurysm were included to the study. Intermittent cold blood and crystalloid cardioplegia were used in 10 patients (group BC) and 9 patients (group CC), respectively. From myocardial biopsies, obtained before and after ischemia, complete electron transport system (ETS) enzyme activities (NDH, SDH, NCCR, SCCR, and COX) and lactate content were analyzed. Biochemical and hemodynamic analyses also were done. Myocardial and blood temperatures were monitored. Ischemic time was longer in group CC (p < 0.05). There were no important differences in biochemical and hemodynamic variables between the two groups. In addition, there was no difference in NDH and SDH activities as well as COX/SCCR and COX/RS‐NCCR ratios between the two groups before and after ischemia. After Ischemia, RS‐NCCR in group CC and SCCR and COX activities in both groups were lower than the control. For all enzymes, activity change ratios were not different between groups. Myocardial lactate content was increased in both groups after ischemia. However, the increase in group BC was less (p < 0.01). Based on our findings, we believe that the superiority of blood cardioplegia over crystalloid cardioplegia does not depend on oxygen content, but on other factors such as buffering and free oxygen radical scavenger effects among others. However, with the warm and continuous blood cardioplegia technique, oxygen content might be more important. Copyright © 1985, Wiley Blackwell. All rights reserved